AN ANALYSIS OF CODE SWITCHING USED IN MASTERCHEF INDONESIA SEASON 6 - michael erikson hutagalung (JURNAL LINER (Language Intelligence and Educational Research), 2021)
Abstract : The purpose of this research are to find out : 1). The types of code switching used in Masterchef Indonesia season 6, 2) the functions of code switching used in Masterchef Indonesia season 6. This research used library research. The informants of this research is all the judges and contestants of Masterchef Indonesia season 6 - Chef Arnold Marah Besar Karena Ini ! and Ini Masterchef Challenge Bukan Paranormal Challenge! gallery 4. In collecting the data, the researcher used documentation technique. The result of the research are 1) 40 data for the types of code switching. 11 data includes inter-sentential of code switching, 28 data includes intra-sentential of code switching, 1 data includes establishing continuity with the previous speaker. 2) The function of code switching in two videos was reiteration and addresse Specification. The use of code switching in two videos is depends on the will and situation of all the judges. Keywords: Code Switching, Masterchef Indonesia, Library Research, Documentation Technique Abstrak : Tujuan dari penelitian ini adalah untuk mengetahui : 1) Tipe alih kode yang digunakan di Masterchef Indonesia season 6, 2) fungsi alih kode yang digunakan di Masterchef indonesia season 6. Penelitian ini menggunakan penelitian pustaka. Dalam pengumpulan data, peneliti menggunakan teknik dokumentasi. Hasil penelitian ini adalah 1) peneliti menemukan ada 40 jenis alih kode. 11 data termasuk inter-sentential of code switching, 28 data termasuk intra-sentential of code switching, 1 data termasuk establishing continuity with the previous speaker . 2) fungsi dari alih kode di video yang pertama dan kedua adalah reiteration dan adresse specification. Penggunaan dari alih kode yang terdapat di kedua video tergantung pada keinginan dan mood dan situasi dari semua juri. Kata kunci: Alih Kode, Masterched Indonesia, penelitian pustaka, teknik dokumentasi